Development of Training Program for Preventing Bad -Purpose Internet of Students in Mathayomsuksa 4 - Chambairak, Chariya; Tayraukham, Assoc. Prof. Dr. Sombat (Journal for Developing the Social and Community, 2019)
The purposes of this study were to 1) create and develop and test the program for self-awareness of using the internet for the bad purpose of Matthayomsuksa 4 students 2) study the result of the program for senior high-school students. The samples of this study were 35 students of a class studying in Matthayomsuksa 4 of Prajacksilapakarn School in the semester 2 of the academic year 2018. They were selected though cluster-random sampling method. They had joined the trainings for 17 times. The research instruments used in the study were the program for self-awareness of using the internet for the bad purpose of senior high-school students and the test of self-awareness of using the internet for the bad purpose containing 40 questions. The test has scale with discriminating power ranging 0.313 - 0.708 and a reliability of 0.980 The statistics used for analyzing the collected data were mean, standard deviation, and One-way repeated measure MANOVA. The study showed that The developed program has 17 activities and takes 8 weeks (2 hours a week) The program for self-awareness of using the internet for the bad purpose of senior high-school students was evaluated by the five experts, and its quality (IOC) was at best level. The students who had joined the training and the follow-up program had the post-test score higher than the pre-test at the 0.01 level of significance. The students who joined the program had the endurance of knowledge in conclusion.